THE ROLE AND THE PLACE OF THE WOMAN IN TURKESTAN ON THE MATERIALS OF THE REPORTS OF SENATORIAL AUDITING OF K.K. PALEN IN 1908-1909 YEARS (ResearchJet Journal of Analysis and Inventions, 2022)
The article deals with the issues of significance and the role of the woman-Moslem, social status of the woman in Turkestan on the materials of the auditing of the senator K.K. Palen